Renal Handling of Galectin‐3 in the General Population, Chronic Heart Failure, and Hemodialysis. Issue 5 (18th September 2014) - Meijers, Wouter C.; van der Velde, A. Rogier; Ruifrok, Willem P.; Schroten, Nicolas F.; Dokter, Martin M.; Damman, Kevin; Assa, Solmaz; Franssen, Casper F.; Gansevoort, Ron T.; van Gilst, Wiek H.; Silljé, Herman H.; de Boer, Rudolf A.
Abstract : Background: Galectin‐3 is a biomarker for prognostication and risk stratification of patients with heart failure (HF). It has been suggested that renal function strongly relates to galectin‐3 levels. We aimed to describe galectin‐3 renal handling in HF. Methods and Results: In Sprague–Dawley rats, we infused galectin‐3 and studied distribution and renal clearance. Furthermore, galectin‐3 was measured in urine and plasma of healthy controls, HF patients and hemodialysis patients. To mimic the human situation, we measured galectin‐3 before and after the artificial kidney. Infusion in rats resulted in a clear increase in plasma and urine galectin‐3. Plasma galectin‐3 in HF patients (n=101; mean age 64 years; 93% male) was significantly higher compared to control subjects (n=20; mean age 58 years; 75% male) (16.6 ng/mL versus 9.7 ng/mL, P <0.001), while urinary galectin‐3 in HF patients was comparable (28.1 ng/mL versus 35.1 ng/mL, P =0.830). The calculated galectin‐3 excretion rate was lower in HF patient (2.3 mL/min [1.5 to 3.4] versus 3.9 mL/min [2.3 to 6.4] in control subjects; P =0.005). This corresponded with a significantly lower fractional excretion of galectin‐3 in HF patients (2.4% [1.7 to 3.7] versus 3.0% [1.9 to 5.5]; P= 0.018). These differences, however, were no longer significant after correction for age, gender, diabetes, and smoking. HF patients who received diuretics (49%) showed significantly higher aldosterone and galectin‐3 levels. Hemodialysis patients (n=105; mean age 63 years; 65% male), without urinary galectin‐3 excretion, had strongly increased median plasma galectin‐3 levels (70.6 ng/mL). Conclusions: In this small cross‐sectional study, we report that urine levels of galectin‐3 are not increased in HF patients, despite substantially increased plasma galectin‐3 levels. The impaired renal handling of galectin‐3 in patients with HF may explain the described relation between renal function and galectin‐3 and may account for the elevated plasma galectin‐3 in HF.